Viability of black oat seeds in the soil as a function of burial time - Kehl, Kassiana; Carvalho, Ivan Ricardo; Sacon, Deivid; Rizzardi, Mauro Antonio; Langaro, Nadia Canali; Huzar, Jaqueline Novakowiski; Loro, Murilo Vieira; Lautenchleger, Francine (Revista de Ciências Agroveterinárias, 2024)
This work aimed to verify if there is a temporal effect on the viability of black oat seeds under natural conditions after harvesting, under burial. The treatments were arranged in a bifactorial scheme, with five black oat genotypes and eight exhumation periods (90; 180; 270; 360; 450; 540; 630 and 720 days after burial), distributed in four repetitions of one hundred seeds buried at 10 cm deep. After each exhumation, seeds separation and count, those that did not germinate, did not rot or were predated were considered as whole seeds, which underwent a process of asepsis and disinfection to verify viability through the germination test and vigor through the tetrazolium test (live seeds). The genotypes showed a decreasing percentage of seeds over time, Agro Planalto showed the lowest percentage at 360 days after burial, Agro Esteio at 450 days, Agro Coxilha, Agro Quaraí and Agro Zebu at 540 days. The percentage of live seeds differed between the genotypes only in the third period of exhumation (270 days after burial), the lowest percentages of live seeds were identified in the genotypes Agro Esteio and Agro Planalto at 360 days after burial, in Agro Coxilha and Agro Quaraí at 450 days and Agro Zebu at 540 days. Black oat seeds remain viable in the soil for a period of 450 days after burial.